The Importance of Specifying The Plaintiff's Boundaries In The Legal Regulations Concerning The Environment In Indonesia - Sulistyowati, Sulistyowati; Otong Rosadi; Ahwan Fanani; Dewi Nadya Maharani (Journal of Law, Politic and Humanities, 2024)
It is important for the government to be actively involved in creating a balanced ecosystem, with the role of the community being a key factor. To maximize the community's contribution, it is recommended that environmental laws grant legal status to non-governmental organizations in this field, enabling them to file dispute resolution applications in the Administrative Court. Non-governmental organizations with legal status that emphasize their goal of preserving the environment can file lawsuits in court, as explained in Decision No. 41/G/LH/2018/PTUN. PBR in the Administrative Court of Pekanbaru, serving as the main subject of this research with a normative juridical approach. In conclusion, challenges arise when the scope of non-governmental organizations in filing lawsuits is too broad, resulting in multiple interpretations and potential harm to other parties. The suggestion is to revise the Environmental Law to address the legal standing limitations of non-governmental organizations as plaintiffs in the Administrative Court, making it more effective in enforcing the law and maintaining ecosystem balance.